Called upstairs : Moravian Inuit music in Labrador - Gordon, Tom, 1946- (McGill-Queen's indigenous and northern series ;, 2023)
"A silent clapboard church on a barren Arctic landscape is more than just a place of worship: it is a symbol that can evoke fraught reactions to the history of Christian colonization. In the Inuit homeland of Northern Labrador, however, that church is more likely to resonate with the voices of a well-rehearsed choir accompanied by an accomplished string orchestra or spirited brass bands. The Inuit making this music are stewards of a tradition of complex sacred music introduced by Moravian missionaries in the late 1700s - a tradition that, over time, these musicians transformed into a cultural expression genuinely their own. Called Upstairs is the story of this Labrador Inuit music practice. It is not principally a story of forced adoption. Rather, it chronicles a process of adaptation, mediation, and agency, exploring the transformation of a colonial artifact into an expression of Inuit aesthetic preference, spirituality, and community identity. Often overlaying the Moravian traditions with defining characteristics drawn from pre-contact expressive culture, Inuit musicians imbued this once-alien music with their own voices. Told through archival documents, oral histories of Inuit musicians, and the music itself, Called Upstairs tracks the emergence of this Labrador Moravian music tradition across two and a half centuries. Tom Gordon presents a chronicle of Inuit leadership and agency in the face of colonialism through a unique lens. In this time of reconciliation, this story offers a window into Inuit resilience and the power of a culture's creative expressions."--